Feasibility of harnessing energy used in copper mining tires by pyrolysis - Flores, Carolina (2016)
In order to respond to the environmental problem of waste used in large quantities generated by copper mining, tire was proposed and experimentally tested, the energy use of the tires based on the thermal decomposition of rubber at high temperatures and in the absence of oxygen, obtaining as results three main products in phases: liquid, gaseous and solid. The pyrolysis experimental work was conducted on two stainless steel cylindrical reactors in series and fed by atmospheric nitrogen. Operating variables studied were: initial mass of raw material, the particle size, the N2 flow rate and temperature in both reactors, resulting in the latter variable has the greatest influence on the characteristics of the products obtained. Finally the technical and environmental feasibility of pyrolysis is demonstrated, proposing an alternative management for tires used in copper mining consists of four main stages: crushing and separation, pyrolysis and electricity cogeneration, which recommended a pilot scale.